Deteksi Salmonella typhi Berbasis Metode PCR pada Terasi Kering Padat Blok Produksi UMKM di Kabupaten Lombok Timur - Ariyana, Mutia Devi; Unsunnidhal, Lalu; Perdhana, Firman Fajar; Febriandito, Muhammad ‘Aidil; Handayani, Baiq Rien; Zuhdia, Lulu Diani (Pro Food, 2025)
Shrimp paste is a fermented shrimp product that is at risk of being contaminated by pathogenic microorganisms, thus potentially causing foodborne diseases. The method for detecting pathogenic microorganisms that has proven to have high specificity and sensitivity in directly detecting the presence of pathogenic bacteria in food samples is the DNA detection method using Polymerase Chain Reaction (PCR). This research aims to detect the presence of pathogenic bacteria, specifically Salmonella typhi, in shrimp paste products produced by several Small and Medium Enterprises (SMEs) in East Lombok Regency using the PCR method. The research samples used were solid block dried shrimp paste from three SMEs in East Lombok Regency. The research results show that the DNA of Salmonella typhi bacteria was not detected in all tested samples. These results indicate that the shrimp paste from the three SMEs in East Lombok has met one of the microbiological quality requirements for shrimp paste based on SNI 2716:2016, which is the absence of Salmonella contamination.